Heha Sky View: Role Model for MSME Partner-Based Tourism in Yogyakarta - Agus Siswanto; Abdul Choliq Hidayat (CV. Ulil Albab Corp, 2024)
This research could be a form of subjective expression that unearths amazing ideas and builds a tourism trade approach through collaboration with Micro, Small and Medium Enterprises (MSMEs). Information gathered through discussions, perceptions, and supplementary sources. Heha Sky View (HSV), located on the slope of Patuk in Yogyakarta, Indonesia, is visited by 15,000 people in a single day during peak season and offers beautiful views, twilight, a variety of Instagram-worthy selfie settings, the mountains, and culinary pleasures. With reasonable costs provided by 25 MSME units connected by skybridge, road nourishment slows down. Another goal of the HSV owner is to use the neighborhood as a buffer zone, benefits for communities, MSMEs, exchanges with multiplier effects, and transport. MSMEs care for, empower, and benefit stakeholders with a capital investment of 10 billion rupiah over a period of 4 (four) years. HSV ought to serve as an example for the tourism industry. The goal is to create sustainable, capital-efficient, and innovative tourism using both natural and manmade scenery. This can serve as an example of role model for Yogyakarta's MSME Partner- Based Tourism.